2022
DOI: 10.3390/genes13101867
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Associated with Prothrombin Time and Activated Partial Thromboplastin Time in Chinese Healthy Population

Abstract: (1) Background: The purpose of this study was to evaluate the effect of gene polymorphisms on prothrombin time (PT) and activated partial thromboplastin time (APTT) in a healthy Chinese population. (2) Methods: A total of 403 healthy volunteers from a series of novel oral anticoagulants (NOACs) bioequivalence trials in China were included. Coagulation tests for PT and APTT were performed in the central lab at Peking University First Hospital. Whole-exome sequencing (WES) and genome-wide association analysis we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 74 publications
0
1
0
Order By: Relevance
“…Furthermore, it has been hypothesized that ZNF594 may influence the usefulness of inhaled 2-adrenergic receptor agonists in the treatment of asthma [ 64 ]. A recent study suggested that the ZNF594 variant may be a new genetic marker for prothrombin time (PT) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been hypothesized that ZNF594 may influence the usefulness of inhaled 2-adrenergic receptor agonists in the treatment of asthma [ 64 ]. A recent study suggested that the ZNF594 variant may be a new genetic marker for prothrombin time (PT) [ 65 ].…”
Section: Discussionmentioning
confidence: 99%